Brazilian red propolis effects on peritoneal macrophage activity: Nitric oxide, cell viability, pro-inflammatory cytokines and gene expression. (31st July 2017) - Bueno-Silva, Bruno; Kawamoto, Dione; Ando-Suguimoto, Ellen S.; Casarin, Renato C.V.; Alencar, Severino M.; Rosalen, Pedro L.; Mayer, Marcia P.A.
Abstract: Ethnopharmacological relevance: Propolis has been used in folk medicine since ancient times and it presented inhibitory effect on neutrophil recruitment previously. However, its effect on macrophage obtained from mice remains unclear. Aim of the study: To demonstrate BRP effects on LPS activated peritoneal macrophage. Materials and Methods: Peritoneal macrophages, obtained from C57BL6 mice and activated with LPS, were treated with 50–80 µg/mL of crude extract of Brazilian red propolis (BRP) during 48 h. Cell viability, levels of NO, 20 cytokines and expression of 360 genes were evaluated. Results: BRP 60 µg/mL reduced NO production by 65% without affecting the cell viability and decreased production IL1α, IL1β, IL4, IL6, IL12p40, Il12p70, IL13, MCP1 and GM-CSF. Molecular mechanism beyond the anti-inflammatory activity may be due to BRP-effects on decreasing expression of Mmp7, Egfr, Adm, Gata3, Wnt2b, Txn1, Herpud1, Axin2, Car9, Id1, Vegfa, Hes1, Hes5, Icam1, Wnt3a, Pcna, Wnt5a, Tnfsf10, Ccl5, Il1b, Akt1, Mapk1, Noxa1 and Cdkn1b and increasing expression of Cav1, Wnt6, Calm1, Tnf, Rb1, Socs3 and Dab2 . Conclusions: Therefore, BRP has anti-inflammatory effects on macrophage activity by reducing NO levels and diminished release and expression of pro-inflammatory cytokine and genes, respectively. Graphical abstract: